Venture Capital and Growth of Small and Medium- Sized Enterprises in Kiambu County, Kenya - Muhuhu , Monicah Wambui; Ngali, Richard; Wepukhulu, Joshua Matanda (International Journal of Finance, 2023)
Purpose: The goal of the study was to look into the impact of Venture Capital financing on the growth of SMEs in Kenya's Kiambu County. The specific objectives included to assess the influence of Venture Capital financial support, Venture Capital managerial support, Venture Capital technical support and attracting other sources of Venture Capital financing on growth of SMEs in Kiambu County. Methodology: To achieve the goals, the study used a descriptive research approach. The target demographic included all 889SMEs in Kiambu County that are listed in the Kiambu Business Directory-(2021). The study used questionnaires and secondary data sheet as the data collection tools. The data collected was coded, quantified, processed and synthesized quantitatively and qualitatively. Findings: The study found that financial support, managerial support, technical support and Venture Capital monitoring affects the growth of SMEs in Kiambu County. The study found that in overall Venture Capital affects the growth of SMEs in Kiambu County to a great extent. The study concludes that financial support offers essential paths for increasing the pool of trained labor, increasing the output of goods and services, creating jobs and providing opportunity to develop entrepreneurial and management abilities. Through Venture Capital managerial support, creative skills, research skills, and strategic technologies are provided which are positively associated with firm growth. Venture Capital monitoring frameworks are responsible for observation of business operations, standard of measurements are crucial in preventing business failures, and vibrant transparency and accountability measures are important in directing enterprises development endeavors. From the inferential analysis, an increase in the Venture Capital financing aspects leads to growth of SMEs in Kiambu County. Unique Contribution to theory, practice and policy: The study recommends the SMEs in the County to partner with Venture Capitalists to benefit from financial support for greater successes. Venture Capital firms and SMEs to work together to form a friendly relationship through multi-party cooperation which will pave way for monitoring of the inputs and outputs of the Venture Capital.